Quality of life and well-being in university students with intellectual disabilities - Nerea Felgueras Custodio; José María López-Díaz; José David Carnicero Pérez (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examined the impact of an intervention applied through the module ‘emotional competencies and personal development’, aimed at university students with intellectual disabilities and autism, with the goal of improving their well-being and self-perceived quality of life. To this end, the INICO-FEAPS scale was used, designed for the multidimensional assessment of quality of life in people with intellectual disabilities. The results showed an improvement in perceived quality of life after the intervention, regardless of the degree of disability, the presence of autism, age or gender. This shows that individualized interventions focused on personal development can promote the well-being of participants, highlighting the importance of programs that strengthen socio-emotional skills and pre-employment preparation. A quasi-experimental design of repeated measures without a control group was used with 14 participants. Pre-post differences were analyzed using the Wilcoxon signed-rank test, estimating effect sizes. Significant improvements were observed in social inclusion, interpersonal relationships, and physical well-being, with high-magnitude effects on overall quality of life indices. Although the findings are preliminary, they provide evidence on the feasibility and potential impact of social-emotional interventions in understudied university contexts.